2021
DOI: 10.3390/nu13113808
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Resistant Starch and Dextrins as Prebiotics: A Review of the Existing Evidence and Clinical Trials

Abstract: In well-developed countries, people have started to pay additional attention to preserving healthy dietary habits, as it has become common knowledge that neglecting them may easily lead to severe health impairments, namely obesity, malnutrition, several cardiovascular diseases, type-2 diabetes, cancers, hypertensions, and inflammations. Various types of functional foods were developed that are enriched with vitamins, probiotics, prebiotics, and dietary fibers in order to develop a healthy balanced diet and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 170 publications
(171 reference statements)
0
19
0
Order By: Relevance
“…[14] In a recent review, resistant starch and resistant dextrins (RD) were proven to have positive effects of body mass index (BMI), total body fat, and markers of metabolic disorders in healthy volunteers. [15] However, not all individuals respond to prebiotics in the same ways. Baseline composition of the gut microbiota is often found to be one of the factors explaining response differences within study-groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] In a recent review, resistant starch and resistant dextrins (RD) were proven to have positive effects of body mass index (BMI), total body fat, and markers of metabolic disorders in healthy volunteers. [15] However, not all individuals respond to prebiotics in the same ways. Baseline composition of the gut microbiota is often found to be one of the factors explaining response differences within study-groups.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] In a recent review, resistant starch and resistant dextrins (RD) were proven to have positive effects of body mass index (BMI), total body fat, and markers of metabolic disorders in healthy volunteers. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…In our review, although we have highlighted the promise offered by a variety of prebiotic supplementations, resistant dextrin has been shown to be the most widely effective in both categories of markers ( 147 , 149 , 152 , 153 ). Resistant dextrins are non-sweet short-chain glucose polymers with high resistance to digestive enzymes of the human gut, up to 75% of which is available for fermentation ( 172 , 190 ). Ślizewska et al have shown that resistant dextrin supplementation among mice was associated with lower levels of Clostridium strain ( 191 ), which is found in elevated levels among diabetics compared to normal gut ( 192 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fermentable fibres can be fermented by specific commensal bacteria of the colon which promotes the maintenance of a healthy intestinal environment and microbiome community. Each fermentable fibre is associated with differing metabolic responses and physiological effect, as the location, speed and type of bacteria involved in the fermentation process varies between fibre type [ 79 , 82 ]. Whilst most fibres tend to be associated with one functional class, they often exert more than one effect, which may be beyond the three classes described.…”
Section: Dietary Fibrementioning
confidence: 99%